'n NUWE PERSPEKTIEF OP DIE SAAMLEEF VAN SOLDATE - Kotzé, H.A. (Scientia Militaria - South African Journal of Military Studies, 2012)
"There are three types of lies: Lies, damn lies and statistics."In this article five views are expressed.1. Typical, quantitative sociological practices are not ideal to foster an understanding of man's cohabitation.2. A new study of cohabitation or another technique of becoming acquainted with groups is needed.3. The military is specially suited to the earlier (mal-?) practices due to its orderly structure _ military sociology was fraught with the earlier stereotype practices.4. The new approach to study is one of actually experiencing and understanding, rather than description and declaration.5. The military (especially the SA Defence Force) is well-suited to the new approach.